2016
DOI: 10.1002/ppul.23523
|View full text |Cite
|
Sign up to set email alerts
|

Complicated community acquired pneumonia in childhood: Different types, clinical course, and outcome

Abstract: NP is a more severe disease with prolonged morbidity and hospitalization in spite of prior antibiotic treatment. All types had favorable outcome regardless of treatment-protocol. Complicated pneumonia has an ethnic predominance. Pediatr Pulmonol. 2017;52:247-254. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
31

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 40 publications
6
41
0
31
Order By: Relevance
“…In agreement with previous studies, all the children presented in this study were pre‐school children (Table ). Other than the young age, we found no other risk factors for the development of giant lung cysts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies, all the children presented in this study were pre‐school children (Table ). Other than the young age, we found no other risk factors for the development of giant lung cysts.…”
Section: Discussionsupporting
confidence: 92%
“…Despite growing numbers of patients with complicated pneumonia, including NP, there is no current consensus regarding how to treat these children due to the lack of large controlled studies. A recent opinion driven article, suggested that children who were classified as suffering from complicated pneumatocele should be treated by image‐guided catheter drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting case‐control study, it was reported that the angiotensin converting enzyme polymorphism rs4340 was associated with increased risk for CAP in Egyptian children . Erlichman et al in Israel reported a retrospective analysis of 144 hospitalized patients over a 10‐year period, with CAP complicated by necrotizing pneumonia, empyema, or parapneumonic effusion . Necrotizing pneumonia tended to be more severe and require longer hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing pneumonia (NP) is a fairly rare but increasing lung infection mostly associated with pleural empyema (94% -97%) [1]- [6].…”
Section: Introductionmentioning
confidence: 99%